Stimulation of aortic smooth muscle cell mitogenesis by serotonin. - Nemecek, G M (1986)
Bovine aortic smooth muscle cells in vitro responded to 1 nM to 10 microM serotonin with increased incorporation of [3H]thymidine into DNA. The mitogenic effect of serotonin was half-maximal at 80 nM and maximal above 1 microM. At a concentration of 1 microM, serotonin stimulated smooth muscle cell mitogenesis to the same extent as human platelet-derived growth factor (PDGF) at 12 ng/ml. Tryptamine was approximately 1/10th as potent as serotonin as a mitogen for smooth muscle cells. Other indoles that are structurally related to serotonin (D- and L-tryptophan, 5-hydroxy-L-tryptophan, N-acetyl-5-hydroxytryptamine, melatonin, 5-hydroxyindoleacetic acid, and 5-hydroxytryptophol) and quipazine were inactive. The stimulatory effect of serotonin on smooth muscle cell DNA synthesis required prolonged (20-24 hr) exposure to the agonist and was attenuated in the presence of serotonin D receptor antagonists. When smooth muscle cells were incubated with submaximal concentrations of serotonin and PDGF, synergistic rather than additive mitogenic responses were observed. These data indicate that serotonin has a significant mitogenic effect on smooth muscle cells in vitro, which appears to be mediated by specific plasma membrane receptors.